Pelanggaran Prinsip Kesantunan Berbahasa Siswa Kelas X MA Nurul Iman dalam Pembelajaran Bahasa Indonesia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the forms of violations of politeness principles committed by tenth-grade students of MA Nurul Iman and to identify the impact of implementing active learning and the habituation of akhlakul karimah on changes in their speech behavior. Observation and utterance analysis were conducted throughout the learning activities, accompanied by the use of various media and active learning strategies. The findings indicate that violations of the six politeness maxims wisdom, generosity, approbation, modesty, agreement, and sympathy still frequently occurred in student interactions, particularly during discussions that triggered spontaneous responses. However, interventions based on akhlakul karimah values, the use of relevant learning media, and the teacher’s role as a model of polite communication were proven effective in reducing the frequency of violations and improving students’ pragmatic awareness. These findings highlight the importance of integrating character education, communication ethics, and active learning methods to foster a polite and constructive language culture within the school environment.